Retrospective analysis of surgical management and aesthetic outcomes in trigonocephaly: A decade of experience - Osman Efe Efeoğlu; Serdar Onur Aydın; Fırat Demir; Lütfi Postalcı; Bekir Can Kendirlioğlu; Gaye Filinte; Evren Aydoğmuş; Tufan Hiçdönmez (World Neurosurgery: X)
Background: This study aims to examine the demographic and clinical data of patients who underwent surgery for trigonocephaly at our clinic to evaluate the characteristics, assess cosmetic outcomes, and compare our results with findings reported in the existing literature. Materials and methods: The clinical records and surgical techniques of patients who underwent surgery for trigonocephaly between 2010 and 2020 were retrospectively analyzed. Preoperative and postoperative photographs of the frontoorbital region were evaluated by two experienced surgeons using the Whitaker Classification to assess cosmetic outcomes. Statistical analysis was performed to compare the assessments made by the surgeons. Results: Among 23 patients (15 males and 8 females), the median age at surgery was 7 months, and the median follow-up period was 6 years. A family history of craniosynostosis was present in 13 % of cases. Preoperative computed tomography (CT) imaging was performed in 57 % of patients, while the remaining were diagnosed clinically. Open reconstruction techniques were employed in all cases. According to the Whitaker Classification, 96 % of patients were categorized in the first two groups (excellent or good outcomes) by both surgeons, showing strong interobserver agreement. Conclusion: Surgical intervention for trigonocephaly not only corrects cranial deformities but also supports proper brain development. Early surgical intervention is recommended to achieve optimal outcomes. The Whitaker Classification serves as a practical tool for standardizing the evaluation of both cosmetic and functional outcomes.